2020
DOI: 10.1080/20013078.2020.1746529
|View full text |Cite|
|
Sign up to set email alerts
|

DUSP2 regulates extracellular vesicle‐VEGF‐C secretion and pancreatic cancer early dissemination

Abstract: Early dissemination is a unique characteristic and a detrimental process of pancreatic ductal adenocarcinoma (PDAC); however, the underlying mechanism remains largely unknown. Here, we investigate the role of dual-specificity phosphatase-2 (DUSP2)-vascular endothelial growth factor-C (VEGF-C) axis in mediating PDAC lymphangiogenesis and lymphovascular invasion. Expression of DUSP2 is greatly suppressed in PDAC, which results in increased aberrant expression of extracellular vesicle (EV)-associated VEGF-C secre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 52 publications
1
36
0
Order By: Relevance
“…Loss of DUSP2 expression correlates with cancer malignancies and constitutive ERK activation (6)(7)(8)19). Recently, we demonstrated that loss-of-DUSP2 promotes pancreatic cancer early dissemination, likely through lymphovasculature (9). In this study, we show that re-expression of DUSP2 is su cient to prevent tumor formation in the orthotopic mouse model of pancreatic cancer.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Loss of DUSP2 expression correlates with cancer malignancies and constitutive ERK activation (6)(7)(8)19). Recently, we demonstrated that loss-of-DUSP2 promotes pancreatic cancer early dissemination, likely through lymphovasculature (9). In this study, we show that re-expression of DUSP2 is su cient to prevent tumor formation in the orthotopic mouse model of pancreatic cancer.…”
Section: Discussionsupporting
confidence: 52%
“…Conditional knockout of Dusp2 in the pancreas is referred to KDC mice (LSL-Kras G12D , Dusp2F/F, Pdx-1-Cre). CRISPR/Cas9 system was used for replacing endogenous mouse dusp2 as described (9). Mice were sacri ced at the age of 6 months and pancreases were harvested for IHC analysis.…”
Section: Animal Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, tumors are not homogeneous, and most authors describe the so-called “autocrine” effect of VEGFC as the effect generated locally, on a specific type of cells—especially tumor cells—bearing the receptors, by the VEGFC secreted by this very type of cells. Paracrine effect is described as an effect occurring when VEGFC is transported by vessels (lymphatics) towards more distant targets 54 56 . To ascertain the autocrine effect of VEGFC, internalization of tagged-VEGFC receptors might be implemented.…”
Section: Discussionmentioning
confidence: 99%
“…PAAD cells secrete several types of cytokines and growth factors such as interleukin (IL)‐6, IL‐8, basic fibroblast growth factor, nerve growth factor and vascular endothelial growth factor. They are implicated in cell proliferation via paracrine or autocrine mechanisms 30‐32 . Therefore, endogenous LPAs and FFAs help transduct the signallings and accelerate cellular growth.…”
Section: Discussionmentioning
confidence: 99%